Analysis of Understory Vegetation in the Pusat Suaka Satwa Elang Jawa Area - Aip Muhamad Irpan; Suci Siti Latifah; Dina Dyah Saputri; Muhamad Alfieansyah; Najla Nurul Amalia (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2025)
Understory vegetation is the basic vegetation of the forest which can include grasses, shrubs, herbs and ferns which make an important contribution to ecological function and biodiversity. It contributes to nutrient cycling, soil stabilization, and forest regeneration. This study aims to analyze the structure of vegetation composition and diversity of understory plants in the Pusat Suaka Satwa Elang Jawa (PSSEJ). The research method uses square transects by determining the research location by purposive sampling. In each square transect, a plot measuring 2.5 m x 2.5 m was made. The number of plots made was 36 plots. The understory plants found were identified by cross-checking with the iNaturalist, PlantNet, Picture This - Plant identifier identification applications. Based on the results of the study, 52 species were found spread across 50 genera and 27 families. The dominant families are the Poaceae and Solanaceae families. The highest importance value index of Pseudechinolaena polystachya from the Poaceae family. The understory plant diversity index with a moderate category. It can be concluded that high species abundance does not always correlate with high INP values.